DENTAL CARIES, GINGIVAL BLEEDING, AND ORAL-HEALTH BEHAVIORS AMONG FIRST-YEAR STUDENTS AT NGUYEN TAT THANH UNIVERSITY, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To estimate the prevalence of dental caries and gingival bleeding and explore associations with socio-demographic and oral-health behaviors among first-year students at Nguyen Tat Thanh University (2025).Subjects and methods: A descriptive cross-sectional analytic study was conducted on 250 first-year students selected by convenience sampling. Oral examinations followed WHO Oral Health Survey (2013) guidelines, recording dental caries using the DMFT index and gingival condition based on the presence of bleeding on probing (BOP). A self-administered questionnaire collected socio-demographic information and oral-health behaviors. Data were analyzed using descriptive statistics, Chi-square tests, and univariable Poisson regression with a significance level of p0) was 67.6% with a mean DMFT of 3.14 ± 2.99 (D: 2.37 ± 2.56; M: 0.24 ± 0.69; F: 0.61 ± 1.38). Gingival bleeding was observed in 68.8% of participants. While 81.2% brushed at least twice daily, 48.8% had never used dental floss and 41.6% had visited a dentist within the past 12 months. No variable was significantly associated with dental caries or gingival bleeding (p>0.05).Conclusion: Dental caries and gingival inflammation remain prevalent among first-year students. Behavioral gaps in interdental cleaning and dental attendance highlight the need for tailored oral-health education and preventive programs at the university level.
Keywords: Dental caries; Gingival bleeding; Oral-health behavior; Students.